PENGARUH FAKTOR PSIKOLOGIS TERHADAP KEPUTUSAN WISATAWAN DALAM MENGUNJUNGI WISATA ZIARAH CHENG BENG DI KABUPATEN KUBU RAYA - admin, SULISTIA B11112056 (Jurnal Manajemen Update, 2016)
This research to analyze the influence of psychological factors on tourist decision in visiting a tourist attraction pilgrimage Cheng Beng in Kubu Raya. The sample was 100 respondents. Sampling was carried out with non-probability sampling method using purposive sampling. Test equipment used to test the research instruments such as validity, reliability and test the classical assumption of normality test, linierity test, multicollinearity test and heteroscedasticity test. For data analysis techniques using multiple linear regression analysis. Hypothesis testing using F test, t test, and determination test. The results showed that psychological factors which consist of motivation, perception, learning, beliefs and attitudes, influence simultaneously toward tourists decision in visiting a pilgrimage Cheng Beng in Kubu Raya. The analysis also showed that partial each variable, motivation, perception, learning, beliefs, and attitudes significantly influence the traveler's decision in visiting a tourist attraction pilgrimage Cheng Beng in Kubu Raya. Keywords: Psychological Factors, Motivation, Perception, Learning, Beliefs And Attitudes, Decision to Visit